2022
DOI: 10.3390/nu14102150
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Paternal Diet on Spermatogenesis and Offspring Health: Focus on Epigenetics and Interventions with Food Bioactive Compounds

Abstract: Infertility is a growing public health problem. Consumption of antioxidant bioactive food compounds (BFCs) that include micronutrients and non-nutrients has been highlighted as a potential strategy to protect against oxidative and inflammatory damage in the male reproductive system induced by obesity, alcohol, and toxicants and, thus, improve spermatogenesis and the fertility parameters. Paternal consumption of such dietary compounds could not only benefit the fathers but their offspring as well. Studies in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 143 publications
(210 reference statements)
0
8
0
Order By: Relevance
“…Another nutritional factor that should be considered when interpreting results of paternal effects studies is macronutrient quality 40 . For example, the relative balance of amino acids within the protein component of diets can influence appetite and metabolic health 41 , and likewise the types of carbohydrates in the diet 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Another nutritional factor that should be considered when interpreting results of paternal effects studies is macronutrient quality 40 . For example, the relative balance of amino acids within the protein component of diets can influence appetite and metabolic health 41 , and likewise the types of carbohydrates in the diet 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Magnesium is an important trace element and activator of many enzymes in the phosphorus transfer reaction; it is involved in spermatogenesis and affects sperm motility ( 113 ). Lower concentrations of magnesium are associated with increased nitric oxide production and vasoconstriction, which may lead to premature ejaculation ( 114 ).…”
Section: Trace Elements Ameliorate Impaired Male Spermatogenesis and ...mentioning
confidence: 99%
“…Research conducted in recent years has shown diet, balanced nutrition to have a significant impact on male fertility (6,7,8). Vitamins, minerals, fatty acids, amino acids, and antioxidants have been shown to increase sperm cell physiology and function through a variety of pathways, including ROS reduction, antioxidant defence system restoration, and inflammation inhibition (6,7,9). Although several studies have implicated diet to play a key role in the improvement of sperm parameters, this is paucity of studies considering the vast field of nutrition.…”
Section: Introductionmentioning
confidence: 99%